Penerapan model pembelajaran problem based learning berbantuan media matific untuk meningkatkan keterampilan pemecahan masalah peserta didik kelas IV sekolah dasar - Putri Rahmadini; Matsuri Matsuri (Didaktika Dwija Indria, 2025)
This study aims to: 1) describe the implementation of the Problem Based Learning (PBL) model assisted by matific media in improving problem-solving skills in multiplication word problems; 2) enhance students’ problem-solving abilities through an interactive and contextual learning approach. The method used was Classroom Action Research (CAR) with the research subjects being one teacher and 21 fourth-grade students. Data collection techniques included observation, questionnaires, documentation, and tests, with data validity ensured through triangulation. Data were analyzed using an interactive analysis approach. The results showed that students' problem-solving skills increased significantly from the pre-action stage (average score of 38,6) to 70,3 in cycle I, and 92,4 in cycle II. Classical mastery also improved from 4,8% to 38,1%, and finally reached 100% in cycle II. The conclusions of the study are: 1) the PBL model assisted by matific media was implemented effectively; 2) the problem-solving skills of fourth-grade students at Tirtoyoso 111 Elementary School improved through the use of this model and media. Theoretically, this research reinforces constructivist theory, emphasizing that active and contextual learning can enhance critical thinking skills. Practically, the findings suggest that teachers can use the PBL model assisted by matific to increase student engagement and learning outcomes in contextual mathematics instruction.This study can be a reference for other researchers.